4BNT162b2 mRNA COVID‐19 vaccine and semen: What do we know?. (8th June 2022) - Olana, Soraya; Mazzilli, Rossella; Salerno, Gerardo; Zamponi, Virginia; Tarsitano, Maria Grazia; Simmaco, Maurizio; Paoli, Donatella; Faggiano, Antongiulio
ABSTRACT: Background: The effects of an mRNA COVID‐19 vaccine on spermatozoa parameters are not known. The aim of this study was to evaluate the effect of the BNT162b2 mRNA COVID‐19 vaccine on human semen, comparing spermatozoa parameters before and after vaccine inoculation. Materials and methods: In this single‐center prospective study, voluntary subjects who received mRNA vaccines from February to July 2021 were enrolled. The study population included male subjects aged between 18 and 45 years who completed the BNT162b2 mRNA COVID‐19 vaccine cycle. All subjects were evaluated before the first dose of vaccine (T0) and after 3 months (T1) with semen analysis and further analysis of seminal plasma, including colorimetric determination of reactive oxygen metabolites (d‐ROM test), electrolytes, and interleukin 6 (IL‐6) assessment by enzyme‐linked immunosorbent assay technology. Results: The experimental sample included 47 subjects (age: 29.3 ± 6.0 years, range 24–32; body mass index: 23.15 ± 2.5 kg/m 2, range 19.2–28.0). All the subjects reported no systemic side effects. No significant differences were observed in any spermatozoa parameter between T0 and T1. A subanalysis was performed in oligoazoospermic and asthenozoospermic subjects, confirming the same results. Electrolyte analysis also showed no significant differences before and after vaccine inoculation. Finally, no significant differences were observed in T0, compared to T1 for the d‐ROM test and IL‐6. Discussion and conclusion: In this study, no significant differences in spermatozoa parameters before and after vaccine inoculations were found. Furthermore, oxidative stress analysis, , the activity of the cell membrane, and IL‐6, as a marker of inflammation, was not affected by the mRNA COVID‐19 vaccine. These results suggest that this vaccine is safe for male semen quality.